Low temperature curable resin composition

By using a specific resin composition to form a color filter film at low temperature, the problem of color resist residue and cured film reliability is solved, and a color filter film with high solvent resistance and reliability is realized.

CN113631586BActive Publication Date: 2025-01-24NISSAN CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080024897.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-03-09
Publication Date
2025-01-24
Estimated Expiration
2040-03-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress the production of color resist residues in color filters at low temperatures, and it is difficult to ensure the solvent resistance and reliability of the cured film.

Method used

Using a resin composition containing a homopolymer of specific structural units, a cross-linking compound, a photoacid generator, a surfactant and an organic solvent, the method is pre-baked, exposed and post-baked at a temperature of 75°C to 110°C. Bake to form the lower film or upper film of the color filter.

Benefits of technology

It achieves the formation of a cured film with excellent solvent resistance and reliability at a temperature not exceeding 110°C, significantly reduces the generation of color resist residue, and improves the quality and yield of color filter devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113631586B_ABST
    Figure CN113631586B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide a resin composition for forming a cured film formed on the lower layer and the upper layer of a color filter. The solution is a resin composition comprising a homopolymer having a structural unit represented by the following formula (1), a crosslinking compound having at least two alkoxyalkyl groups in one molecule, a photoacid generator, a surfactant, and an organic solvent, wherein the content of the crosslinking compound is 40% to 60% by mass relative to the content of the homopolymer, and the content of the photoacid generator is at least 0.8% by mass relative to the sum of the contents of the homopolymer and the crosslinking compound. (In the above formula, R 1 represents an alkyl group having 1 to 6 carbon atoms and having at least one hydroxyl group as a substituent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition used for forming a cured film formed on a lower layer and an upper layer of a color filter in a device having a color filter such as an image sensor or a display device, and particularly relates to a low-temperature curable resin composition capable of forming a cured film at a baking temperature not exceeding 110°C. Background Art

[0002] In recent years, color filters have become one of the essential components in devices such as CCD image sensors, CMOS image sensors, liquid crystal displays, and organic EL displays.

[0003] Generally speaking, a transparent resin film such as a protective film or a flattening film is formed on the upper layer of the color filter for the purpose of protecting the color filter and smoothing the unevenness on the color filter surface. In addition, a transparent resin film is also formed on the lower layer of the color filter for the purpose of improving the adhesion between the color filter and the base substrate and smoothing the unevenness caused by the existence of the circuit wiring part, the shading film, the inner lens, etc. The composition for forming such a transparent resin film is disclosed in, for example, Patent Documents 1 to 4.

[0004] In the formation of the color filter, for example, a color resist containing three colors of red, green and blue, for example, a pigment or dye is generally used. The method for forming the color filter using the three-color color resist is to first apply the color resist of the first color, perform exposure, development, and heat treatment, and form a color resist pattern of the first color. Then, the color resist patterns of the second color and the third color are formed in the same manner as the color resist pattern of the first color, thereby forming the color filter.

[0005] In such a color filter forming method, in order to suppress degradation of color reproducibility of the color filter and reduction in yield of devices including the color filter, it is important to suppress generation of color resist residues when forming a color resist pattern.

[0006] It is desirable that the organic EL display device is manufactured by a process at a lower temperature than other devices. For example, as disclosed in Patent Document 5, in order to maintain the characteristics of the organic EL element, it is required not to apply a temperature higher than 110° C. Therefore, the transparent resin film formed on the upper and lower layers of the color filter needs to be formed by curing the resin composition at a temperature below 110° C.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2000-344866

[0010] Patent Document 2: Japanese Patent Application Publication No. 2008-031370

[0011] Patent Document 3: Japanese Patent No. 4222457

[0012] Patent Document 4: International Publication No. 2013 / 005619

[0013] Patent Document 5: International Publication No. 2017 / 203885 Summary of the invention

[0014] Problems to be solved by the invention

[0015] When a color filter is formed on the transparent resin film, the transparent resin film is required to have the above-mentioned property of suppressing the generation of color resist residues. However, the transparent resin film formed of a conventional low-temperature curing material has the problem of not having both a sufficient suppressing effect on the generation of color resist residues and sufficient reliability as a permanent film.

[0016] The present invention has been made based on the above circumstances, and its object is to provide a resin composition that can form a cured film having excellent solvent resistance and reliability at a temperature not exceeding 110° C., preferably 100° C. or less, can suppress the generation of color resist residue when a color filter is formed on the cured film, and can form the cured film on the color filter. Another object of the present invention is to provide a method for producing a device having a color filter having a color filter lower layer film and / or a color filter upper layer film having excellent solvent resistance and reliability.

[0017] Methods for solving problems

[0018] The inventors of the present invention have conducted intensive studies to solve the above problems and have completed the present invention. That is, the present invention is a resin composition comprising a homopolymer having a structural unit represented by the following formula (1), a crosslinking compound having at least two alkoxyalkyl groups in one molecule, a photoacid generator, a surfactant, and an organic solvent, wherein the content of the crosslinking compound is 40% to 60% by mass relative to the content of the homopolymer, and the content of the photoacid generator is at least 0.8% by mass relative to the sum of the contents of the homopolymer and the crosslinking compound.

[0019]

[0020] (In the above formula, R 1 represents an alkyl group having 1 to 6 carbon atoms and having at least one hydroxyl group as a substituent.

[0021] The acid generated by the photoacid generator is, for example, a superacid, and its acid dissociation constant pKa is, for example, less than -7.

[0022] The acid generated by the above-mentioned photoacid generator is, for example, a Bronsted acid.

[0023] The photoacid generator is, for example, N-(trifluoromethanesulfonyloxy)-1,8-naphthalimide or a derivative thereof, or a diphenyl[4-(phenylthio)phenyl]sulfonium salt compound.

[0024] Another embodiment of the present invention is a method for producing a device having a color filter, which comprises the following steps: a step of coating the resin composition of the present invention on a substrate; a step of pre-baking the resin composition at 75°C to 110°C, exposing it to near-ultraviolet light, and then post-baking it at 75°C to 110°C to form a color filter lower film; and a step of forming a color filter on the above-mentioned color filter lower film using a color resist.

[0025] The method for producing the device having a color filter may further include the following steps: a step of coating the resin composition on the color filter; and a step of pre-baking the resin composition at 75°C to 110°C, exposing it to near-ultraviolet light, and then post-baking it at 75°C to 110°C to form an upper film of the color filter.

[0026] The above-mentioned pre-baking and post-baking are preferably performed at 100° C. or lower.

[0027] Effects of the Invention

[0028] The color filter lower film or the color filter upper film formed by the resin composition of the present invention has excellent chemical resistance, heat resistance and transparency. Thus, the color filter lower film or the color filter upper film formed by the resin composition of the present invention can significantly reduce the possibility of element degradation or damage in the process of forming the process or the formation process of peripheral devices such as wiring, when exposed to the treatment of the liquid such as acid or alkaline solution or solvent, and exposed to the treatment of sputtering and dry etching. In addition, in the case of forming the color filter lower film by the resin composition of the present invention and applying the color resist thereon, the problem of mixing with the color resist, the problem of the residue of the color resist, and the deformation and peeling of the color filter lower film caused by the above-mentioned liquid can also be significantly reduced. Further, the color filter lower film or the color filter upper film formed by the resin composition of the present invention can be developed by using an alkaline developer after exposure, so as to form a desired pattern. Therefore, the resin composition of the present invention is suitable as a material for forming the color filter lower film or the color filter upper film. DETAILED DESCRIPTION

[0029] The present invention is a resin composition containing a specific homopolymer, a crosslinking compound having at least two alkoxyalkyl groups in one molecule, a photoacid generator, a surfactant, and an organic solvent. The details of each component are described below. The solid content after removing the organic solvent from the resin composition of the present invention is usually 0.01% by mass to 50% by mass.

[0030] <Homopolymer>

[0031] The homopolymer contained in the resin composition of the present invention is a polymer having a structural unit represented by the above formula (1). 1 As the group represented by , there can be mentioned, for example, a hydroxymethyl group, a hydroxyethyl group, a hydroxypropyl group, a hydroxybutyl group, a dihydroxypropyl group, and a dihydroxybutyl group.

[0032] Examples of the compound (monomer) forming the structural unit represented by the above formula (1) include hydroxymethyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 2,3-dihydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 4-hydroxybutyl methacrylate, 3,4-dihydroxybutyl methacrylate, diethylene glycol monomethacrylate, and dipropylene glycol monomethacrylate. By using a homopolymer having the structural unit represented by the formula (1) in the resin composition of the present invention, after a color filter is formed on the color filter underlayer film formed by the resin composition, the residue of the color resist generated on the color filter underlayer film can be suppressed.

[0033] The weight average molecular weight of the homopolymer is usually 1,000 to 200,000, preferably 3,000 to 100,000. The weight average molecular weight is a value obtained by gel permeation chromatography (GPC).

[0034] The content of the homopolymer in the resin composition of the present invention is usually 30% by mass to 99% by mass, and preferably 60% by mass to 75% by mass, based on the solid content of the resin composition.

[0035] In the present invention, the method for obtaining the above homopolymer is not particularly limited, and generally, it is obtained by subjecting the compound (monomer) forming the structural unit represented by the above formula (1) to polymerization reaction in a solvent in the presence of a polymerization initiator, usually at a temperature of 50° C. to 120° C. The homopolymer obtained in this way is usually in a solution state dissolved in a solvent, and can also be used in the resin composition of the present invention in this state without isolation.

[0036] In addition, the solution of the homopolymer obtained by the above-mentioned operation is put into a poor solvent such as hexane, ether, toluene, methanol, water, etc. that has been stirred to reprecipitate the homopolymer, and the generated precipitate is decanted or filtered, and after washing as required, it is dried at normal temperature or heated and dried under normal pressure or reduced pressure, so that the homopolymer can be made into an oily substance or a powder. By such operation, the polymerization initiator and the unreacted compound coexisting with the above-mentioned homopolymer can be removed. In the present invention, the oily substance or the powder of the homopolymer can be directly used, or the oily substance or the powder can be redissolved in, for example, an organic solvent described later and used as a solution.

[0037] <Cross-linking compounds>

[0038] The crosslinkable compound contained in the resin composition of the present invention has at least two alkoxyalkyl groups in one molecule. Examples of the crosslinkable compound include compounds having a nitrogen atom alkylated with an alkoxy group.

[0039] Examples of the above-mentioned compounds having an alkoxyalkylated nitrogen atom include nitrogen-containing compounds having a plurality of active methylol groups in one molecule, such as (poly)methylolated melamine, (poly)methylolated glycoluril, (poly)methylolated benzoguanamine, and (poly)methylolated urea, and compounds in which at least one of the hydrogen atoms of the hydroxyl group in the methylol group is substituted with an alkyl group such as a methyl group or a butyl group.

[0040] The above-mentioned compound having a nitrogen atom alkylated with an alkoxy group may be a mixture of a plurality of substituted compounds, or a mixture containing a part of oligomer components formed by self-condensation, and such a mixture may be used. More specifically, for example, hexamethoxymethylmelamine (manufactured by Japan Science Instruments Co., Ltd., CYMEL [registered trademark] 303), tetrabutoxymethyl glycoluril (manufactured by Japan Science Instruments Co., Ltd., CYMEL [registered trademark] 1170), tetramethoxymethylbenzoguanamine (manufactured by Japan Science Instruments Co., Ltd., CYMEL [registered trademark] 1123) and other CYMEL series products, tetramethoxymethyl glycoluril (manufactured by Japan Science Instruments Co., Ltd., CYMEL [registered trademark] 1170), and tetramethoxymethylbenzoguanamine (manufactured by Japan Science Instruments Co., Ltd., CYMEL [registered trademark] 1170) may be mentioned. , POWDERLINK [registered trademark] 1174) and other POWDERLINK series products, and methylated melamine resins ((Sanwa Chemical Co., Ltd., Nicolack [registered trademark] MW-30HM, Nicolack MW-390, Nicolack MW-100LM, Nicolack MX-750LM), methylated urea resins ((Sanwa Chemical Co., Ltd., Nicolack [registered trademark] MX-270, Nicolack MX-280, Nicolack MX-290) and other Nicolack series products. These crosslinking compounds may be used alone or in combination of two or more.

[0041] The content of the crosslinking compound in the resin composition of the present invention is preferably 40% to 60% by mass based on the content of the homopolymer in the resin composition. When the content of the crosslinking compound in the resin composition of the present invention is excessive or insufficient, after a color filter is formed on the color filter underlayer film formed from the resin composition, more color resist residue may be observed on the color filter underlayer film.

[0042] <Photoacid generator>

[0043] The photoacid generator contained in the resin composition of the present invention is a compound that generates a strong acid upon exposure, preferably a compound that generates a superacid having an acid dissociation constant pKa of less than -7. Specific examples of such compounds include Salt compounds, sulfonimide compounds, and disulfonyldiazomethane compounds.

[0044] As the above Specific examples of salt compounds include diphenyl iodide Hexafluorophosphate, diphenyl iodide Trifluoromethanesulfonate, diphenyl iodide Nonafluoro-n-butane sulfonate, diphenyl iodide Perfluoro-n-octane sulfonate, diphenyl iodide Camphorsulfonate, bis(4-tert-butylphenyl)iodide Camphorsulfonate, bis(4-tert-butylphenyl)iodide Trifluoromethanesulfonate and other iodine Sulfonium salt compounds, and triphenylsulfonium hexafluorophosphate, triphenylsulfonium tris(pentafluoroethyl) trifluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetra(pentafluorophenyl)borate, triphenylsulfonium nonafluoro-n-butanesulfonate, triphenylsulfonium camphorsulfonate, triphenylsulfonium trifluoromethanesulfonate, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluorophosphate, diphenyl[4-(phenylthio)phenyl]sulfonium tris(pentafluoroethyl) trifluorophosphate, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluoroantimonate, diphenyl[4-(phenylthio)phenyl]sulfonium tetra(pentafluorophenyl)borate and the like. Among the onium salt compounds, sulfonium salt compounds are preferred, and as compounds that generate an acid by exposure to i-rays (365 nm), diphenyl[4-(phenylthio)phenyl]sulfonium salt compounds are more preferred.

[0045] Specific examples of the sulfonyl imide compounds include N-(trifluoromethanesulfonyloxy)succinimide, N-(nonafluoro-n-butanesulfonyloxy)succinimide, N-(camphorsulfonyloxy)succinimide, N-(trifluoromethanesulfonyloxy)-1,8-naphthalene dicarboximide, N-(trifluoromethanesulfonyloxy)-2-alkyl-1,8-naphthalene dicarboximide, N-(trifluoromethanesulfonyloxy)-3-alkyl-1,8-naphthalene dicarboximide, and N-(trifluoromethanesulfonyloxy)-4-alkyl-1,8-naphthalene dicarboximide. Among the sulfonyl imide compounds, N-(trifluoromethanesulfonyloxy)-1,8-naphthalene dicarboximide and its derivatives are preferred.

[0046] Specific examples of the disulfonyldiazomethane compound include bis(trifluoromethylsulfonyl)diazomethane.

[0047] Specific examples of the above-mentioned photoacid generator include Abeka (registered trademark) SP-056 and AbekaークルズSP-066、アデカアークルズSP-140、アデカアークルズSP-141、アデカアークルズSP-082, アデカアークルズSP-601, アデカアークルズSP-6 06. アデカアークルズSP-701, アデカアークルズSP-150, アデカアークルズS P-170, ADEKA ACLUZ SP-171 (all manufactured by ADEKA Co., Ltd.), CPI (registered trademark)-110P, CPI-110B, CPI-310B, CPI-210S, CPI-100P, CPI-101A, CPI-200K (all manufactured by Sanapro Co., Ltd.), DPI-105, DPI-106, DPI-109, DPI-201, BI-105, MPI-105, MPI-201 I-106, MPI-109, BBI-102, BBI-103, BBI-105, BBI-106, BBI-109, BBI-110, BBI-200, BBI-201, BBI-3 00, BBI-301, TPS-102, TPS-103, TPS-105, TPS-106, TPS-109, TPS-200, TPS-300, TPS-1000, HDS-109 , MDS-103, MDS-105, MDS-205, MDS-209, BDS-109, MNPS-109, DTS-102, DTS-103, DTS-105, DTS-200, NDS-103, NDS-105, NDS-155, NDS-165, SI-105, NDI-105, NDI-109, NAI-105, NAI-109 (all manufactured by Midori Chemical Co., Ltd.). These photoacid generators may be used alone or in combination of two or more.

[0048] In addition, the content of the photoacid generator in the resin composition of the present invention is generally 0.8% to 20% by mass, preferably 1.0% to 15% by mass, based on the sum of the contents of the homopolymer and the crosslinking compound in the resin composition. If the content of the photoacid generator in the resin composition of the present invention is too small, the solvent resistance or reliability of the film formed from the resin composition may become insufficient.

[0049] <Surfactant>

[0050] The resin composition of the present invention contains a surfactant for the purpose of improving coating properties. Examples of the surfactant include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether, polyoxyethylene alkyl aryl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether, polyoxyethylene / polyoxypropylene block copolymers, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate, and sorbitan tristearate. Nonionic surfactants such as polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tristearate, etc., EFTOP EF301 (registered trademark), EFTOP EF303, EFTOP EF352 (all manufactured by Mitsubishi Material Electronics Co., Ltd.), Megapuck (registered trademark) 〕F-171、メガファックF-173、メガファックR-30、メガファックR-40、メガファックR-40-LM (above, manufactured by DIC Co., Ltd.), フロラードFC430, フロラードFC431 (above) , manufactured by Sumitomo Solar (Co., Ltd.), アサヒガード [registered trademark] AG710, サーフロン [registered trademark] S- 382. サーフロンSC101, サーフロンSC102, サーフロンSC103, サーフロンSC10 4. Fluorine-based surfactants such as Surflon SC105, Surflon SC106 (manufactured by AGC Co., Ltd.), FTX-206D, FTX-212D, FTX-218, FTX-220D, FTX-230D, FTX-240D, FTX-212P, FTX-220P, FTX-228P, FTX-240G, and DFX-18 (manufactured by Neos Co., Ltd.), and organosiloxane polymer KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.). These surfactants may be used alone or in combination of two or more.

[0051] The content of the surfactant in the resin composition of the present invention is usually 0.001 to 3% by mass, preferably 0.01 to 2% by mass, and more preferably 0.1 to 1% by mass, based on the content of the homopolymer in the resin composition.

[0052] <Organic solvents>

[0053] As the organic solvent included in the resin composition of the present invention, there is no particular limitation as long as it is an organic solvent that dissolves the solid content included in the resin composition. As such an organic solvent, for example, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, methyl cellosolve acetate, ethyl cellosolve acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, propylene glycol monoethyl ether acetate, propylene glycol propyl ether acetate, propylene glycol monobutyl ether, propylene glycol monobutyl ether acetate, toluene, xylene, methyl ethyl ketone, cyclopentane Ketone, cyclohexanone, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl ethoxylate, ethyl hydroxylate, methyl 2-hydroxy-3-methylbutyrate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, 2-heptanone, γ-butyrolactone, N-methylpyrrolidone, and N-ethylpyrrolidone. These organic solvents can be used alone or in combination of two or more.

[0054] Among the above-mentioned organic solvents, from the viewpoint of improving the leveling property of the coating film formed by applying the resin composition of the present invention on a substrate, preferred are propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, propylene glycol monopropyl ether, 2-heptanone, ethyl lactate, butyl lactate, cyclopentanone, cyclohexanone and γ-butyrolactone.

[0055] <Other additives>

[0056] The resin composition of the present invention may contain additives such as a light stabilizer, an ultraviolet absorber, a sensitizer, a plasticizer, an antioxidant, an adhesion promoter, and a defoaming agent as necessary, unless the effects of the present invention are impaired.

[0057] <Method for preparing resin composition>

[0058] The method for preparing the resin composition of the present invention is not particularly limited, and examples thereof include a method of dissolving a solution of a homopolymer having a structural unit represented by the above formula (1), a crosslinking compound, a photoacid generator, and a surfactant in an organic solvent at a predetermined ratio to prepare a uniform solution. Furthermore, examples thereof include a method of further adding and mixing other additives as needed at an appropriate stage of the preparation method.

[0059] <Method for producing color filter lower layer film or color filter upper layer film>

[0060] The method for making a color filter lower film or a color filter upper film using the resin composition of the present invention is described. The resin composition of the present invention is applied to a substrate (for example, a semiconductor substrate, a glass substrate, a quartz substrate, a silicon wafer, and a substrate on which various metal films, planarization films, color filters, organic EL elements, etc. are formed on their surfaces) by a spin coater, a coater, or other appropriate coating method, and then pre-baked using a heating device such as a hot plate or an oven to form a coating film. The coating film is then exposed using an exposure machine. Further, a post-baking is performed using a heating device such as a hot plate or an oven to cure it, and a color filter lower film or a color filter upper film is produced. After the above-mentioned resin composition is applied or pre-baked, a development process may be included. The above-mentioned pre-baking and post-baking conditions are appropriately selected from a baking temperature of 75°C to 110°C and a baking time of 0.3 minutes to 60 minutes. The post-baking may be performed in more than two steps. In the above-mentioned exposure, for example, near ultraviolet rays (such as i-rays) may be used. The color filter lower layer film formed from the resin composition of the present invention has a thickness of, for example, 0.06 μm to 0.5 μm, and the color filter upper layer film formed from the resin composition of the present invention has a thickness of, for example, 0.3 μm to 1.0 μm.

[0061] Example

[0062] The present invention will be described in more detail below based on Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0063] [Measurement of weight average molecular weight of homopolymer obtained in the following synthesis example]

[0064] The molecular weight of the homopolymer was measured by a GPC apparatus, and the weight average molecular weight (Mw) was calculated as a value converted into polyethylene glycol or polyethylene oxide.

[0065] GPC apparatus: Showa Denko GPC system (Shodex [registered trademark] GPC-101) Column: Shodex [registered trademark] KD-800RH, KD-800RL, KD-803 and KD-805 Column temperature: 50°C

[0066] Eluent: N,N-dimethylformamide [as an additive, containing lithium bromide monohydrate (LiBr·H 2 O) 30mmol / L, phosphoric acid anhydrous crystals (o-phosphoric acid) 30mmol / L, and tetrahydrofuran (THF) 10ml / L.]

[0067] Flow rate: 1.0mL / min

[0068] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide manufactured by Tosoh Corporation [weight average molecular weight (Mw) 900,000, 150,000, 100,000, 30,000], and polyethylene glycol manufactured by Polymer Laboratory Co., Ltd. [peak molecular weight (Mp) 12,000, 4,000, 1,000]

[0069] In order to avoid peak overlap, two samples were measured: a sample obtained by mixing four types of standard polyethylene oxides with Mw of 900,000 and 100,000 and polyethylene glycols with Mp of 12,000 and 1,000; and a sample obtained by mixing three types of standard polyethylene oxides with Mw of 150,000 and 30,000 and polyethylene glycol with Mp of 4,000.

[0070] [Synthesis of polymer]

[0071] <Synthesis example 1>

[0072] After dissolving 40.0 g of 2-hydroxyethyl methacrylate and 3.0 g of 2,2'-azobisisobutyronitrile in 80.0 g of propylene glycol monomethyl ether, the solution was added dropwise over 4 hours to a flask containing 49.0 g of propylene glycol monomethyl ether at 70°C. After the addition was completed, the mixture was further reacted for 18 hours to obtain a homopolymer solution (solid content concentration 25% by mass). The weight average molecular weight Mw of the obtained homopolymer was 24,200.

[0073] <Synthesis example 2>

[0074] After dissolving 30.2 g of 2-hydroxypropyl acrylate, 10.0 g of benzyl acrylate and 3.4 g of 2,2'-azobisisobutyronitrile in 80.9 g of propylene glycol monomethyl ether, the solution was added dropwise over 4 hours to a flask containing 49.8 g of propylene glycol monomethyl ether at 70°C. After the addition was completed, the mixture was further reacted for 18 hours to obtain a copolymer solution (solid content concentration 25.0% by mass). The weight average molecular weight Mw of the obtained copolymer was 13,500.

[0075] [Preparation of resin composition]

[0076] <Example 1>

[0077] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 0.8 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking compound, 0.028 g of SP-606 (manufactured by ADEKA Corporation) as a photoacid generator, and 0.002 g of Megafac [registered trademark] R-40 (manufactured by DIC Corporation) were dissolved in 13.9 g of propylene glycol monoethyl ether and 26.3 g of propylene glycol monomethyl ether to prepare a solution. Then, the solution was filtered using a PTFE microfilter having a pore size of 1.0 μm to prepare a resin composition.

[0078] <Example 2>

[0079] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 0.8 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking compound, 0.14 g of CPI-210S (manufactured by Sanapro Co., Ltd.) as a photoacid generator, and 0.002 g of Megaphage [registered trademark] R-40 (manufactured by DIC Corporation) were dissolved in 13.9 g of propylene glycol monoethyl ether and 26.3 g of propylene glycol monomethyl ether to prepare a solution. Then, the solution was filtered using a PTFE microfilter having a pore size of 1.0 μm to prepare a resin composition.

[0080] <Example 3>

[0081] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 0.8 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking compound, 0.14 g of CPI-110B (manufactured by Sanapro Co., Ltd.) as a photoacid generator, and 0.002 g of Megaphage [registered trademark] R-40 (manufactured by DIC Corporation) were dissolved in 13.9 g of propylene glycol monoethyl ether and 26.3 g of propylene glycol monomethyl ether to prepare a solution. Then, the solution was filtered using a PTFE microfilter having a pore size of 1.0 μm to prepare a resin composition.

[0082] <Example 4>

[0083] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 1.2 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking compound, 0.032 g of SP-606 (manufactured by ADEKA Corporation) as a photoacid generator, and 0.002 g of Megafac [registered trademark] R-40 (manufactured by DIC Corporation) were dissolved in 15.8 g of propylene glycol monoethyl ether and 30.9 g of propylene glycol monomethyl ether to prepare a solution. Then, the solution was filtered using a PTFE microfilter having a pore size of 1.0 μm to prepare a resin composition.

[0084] <Comparative Example 1>

[0085] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 0.8 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking compound, 0.028 g of TAG2689 (manufactured by King Industries) as a thermal acid generator, and 0.002 g of Megafac [registered trademark] R-40 (manufactured by DIC Corporation) were dissolved in 13.9 g of propylene glycol monoethyl ether and 26.3 g of propylene glycol monomethyl ether to prepare a solution. Then, the solution was filtered using a PTFE microfilter having a pore size of 1.0 μm to prepare a resin composition.

[0086] <Comparative Example 2>

[0087] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 0.8 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking compound, 0.028 g of p-toluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) as an acid compound, and 0.002 g of Megaphage [registered trademark] R-40 (manufactured by DIC Corporation) were dissolved in 13.9 g of propylene glycol monoethyl ether and 26.3 g of propylene glycol monomethyl ether to prepare a solution. Then, the solution was filtered using a PTFE microfilter having a pore size of 1.0 μm to prepare a resin composition.

[0088] <Comparative Example 3>

[0089] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 0.8 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.)) as a crosslinking compound, and pyridine as an acid compound were added. 0.028 g of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 0.002 g of Megafuk R-40 (manufactured by DIC Corporation) were dissolved in 13.9 g of propylene glycol monoethyl ether and 26.3 g of propylene glycol monomethyl ether to prepare a solution. The solution was then filtered using a PTFE microfilter having a pore size of 1.0 μm to prepare a resin composition.

[0090] <Comparative Example 4>

[0091] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 0.8 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.)) as a crosslinking compound, and pyridine as an acid compound were added. 0.14 g of p-toluenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 0.002 g of Megafuk R-40 (manufactured by DIC Corporation) were dissolved in 14.4 g of propylene glycol monoethyl ether and 27.6 g of propylene glycol monomethyl ether to prepare a solution. The solution was then filtered using a PTFE microfilter having a pore size of 1.0 μm to prepare a resin composition.

[0092] <Comparative Example 5>

[0093] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 0.2 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking compound, 0.022 g of SP-606 (manufactured by ADEKA Co., Ltd.) as a photoacid generator, and 0.002 g of Megafac [registered trademark] R-40 (manufactured by DIC Co., Ltd.) were dissolved in 10.9 g of propylene glycol monoethyl ether and 19.4 g of propylene glycol monomethyl ether to prepare a solution. Then, the solution was filtered using a PTFE microfilter with a pore size of 1.0 μm to prepare a resin composition. This comparative example is an example in which the content of the crosslinking compound is too small.

[0094] <Comparative Example 6>

[0095] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 1.6 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking compound, 0.036 g of SP-606 (manufactured by ADEKA Co., Ltd.) as a photoacid generator, and 0.002 g of Megafac [registered trademark] R-40 (manufactured by DIC Co., Ltd.) were dissolved in 17.8 g of propylene glycol monoethyl ether and 35.6 g of propylene glycol monomethyl ether to prepare a solution. Then, the solution was filtered using a PTFE microfilter with a pore size of 1.0 μm to prepare a resin composition. This comparative example is an example in which the content of the crosslinking compound is excessive.

[0096] <Comparative Example 7>

[0097] 8.0 g of the homopolymer solution obtained in Synthesis Example 1, 0.4 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking compound, 0.024 g of SP-606 (manufactured by ADEKA Co., Ltd.) as a photoacid generator, and 0.002 g of Megafac [registered trademark] R-40 (manufactured by DIC Co., Ltd.) were dissolved in 11.9 g of propylene glycol monoethyl ether and 21.7 g of propylene glycol monomethyl ether to prepare a solution. Then, the solution was filtered using a PTFE microfilter with a pore size of 1.0 μm to prepare a resin composition. This comparative example is an example in which the content of the crosslinking compound is too small.

[0098] <Comparative Example 8>

[0099] 8.0 g of the solution of the copolymer obtained in Synthesis Example 2, 0.8 g of tetramethoxymethyl glycoluril (POWDERLINK [registered trademark] 1174 (manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking compound, 0.028 g of SP-606 (manufactured by ADEKA Corporation) as a photoacid generator, and 0.002 g of Megafac [registered trademark] R-40 (manufactured by DIC Corporation) were dissolved in 13.9 g of ethyl lactate and 26.3 g of propylene glycol monomethyl ether to prepare a solution. Then, the solution was filtered using a PTFE microfilter having a pore size of 1.0 μm to prepare a resin composition.

[0100] [Solvent resistance test]

[0101] The resin compositions prepared in Examples 1 to 4 and Comparative Examples 1 to 8 were applied onto silicon wafers using a spin coater, baked on a hot plate at 100° C. for 1 minute, and exposed at 500 mJ / cm using an i-ray stepper NSR-2205i12D (NA=0.63) (manufactured by Nikon Corporation).2 The films were exposed and further baked at 100°C for 9 minutes to form films with a thickness of 0.2 μm. These films were immersed in propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, ethyl 3-ethoxypropionate, cyclohexanone and a 2.38 mass % aqueous solution of tetramethylammonium hydroxide (hereinafter referred to as TMAH) at a temperature of 23°C for 5 minutes, and then dried and baked at 100°C for 1 minute. The film thickness of the film before immersion and the film after drying and baking were measured, and the film thickness change rate was calculated by the following formula.

[0102] [1-(film thickness after drying and baking / film thickness before immersion)]×100(%)

[0103] The solvent resistance was evaluated as "×" when the film thickness change rate in any one of the immersion solvents was 10% or more, and "○" when the film thickness change rate in all the solvents was less than 10%. The evaluation results are shown in Table 1.

[0104] [Transmittance measurement]

[0105] The resin compositions prepared in Examples 1 to 4 and Comparative Examples 1 to 8 were applied onto a quartz substrate using a spin coater, baked on a hot plate at 100° C. for 1 minute, and exposed at 500 mJ / cm using an i-ray stepper NSR-2205i12D (NA=0.63) (manufactured by Nikon Corporation). 2 The films were exposed and baked at 100°C for 9 minutes to form films with a thickness of 0.2 μm. The films were measured for transmittance by changing the wavelength by 2 nm in the range of 400 nm to 800 nm using an ultraviolet-visible spectrophotometer UV-2550 (manufactured by Shimadzu Corporation). The minimum transmittance values ​​measured in the range of 400 nm to 800 nm are shown in Table 1.

[0106] [Reliability test]

[0107] The resin compositions prepared in Examples 1 to 4 and Comparative Examples 2 to 6 were applied onto silicon wafers using a spin coater, baked on a hot plate at 100° C. for 1 minute, and exposed at 500 mJ / cm using an i-ray stepper NSR-2205i12D (NA=0.63) (manufactured by Nikon Corporation). 2 The film was exposed and further baked at 100°C for 9 minutes to form a film with a thickness of 0.2 μm. The obtained film was exposed to air at 90°C for 240 hours, and a reliability test was performed. The film thickness of the film before and after the test was measured using an interference film thickness meter. The film thickness change rate was calculated by the following formula, and when the film thickness change rate exceeded 5%, it was evaluated as "×", and when the film thickness change rate was less than 5%, it was evaluated as "○". The evaluation results are shown in Table 1.

[0108] [1-(film thickness after test / film thickness before test)]×100(%)

[0109] [Color resist residue]

[0110] The resin compositions prepared in Example 1, Example 4, and Comparative Examples 5 to 8 were respectively applied to silicon wafers using a spin coater, and exposed on a hot plate at 100° C. for 1 minute using an i-ray stepper exposure machine NSR-2205i12D (NA=0.63) (manufactured by Nikon Corporation), and further baked on a hot plate at 100° C. for 9 minutes to form a color filter lower layer film with a film thickness of 0.2 μm. On the color filter lower layer film, a photo-radical polymerizable pigment dispersion type red color resist liquid containing CI Pigment Red 254 and CI Pigment Red 177 as pigments was applied, and baked on a hot plate at 100° C. for 1 minute to form a red color resist film with a film thickness of 0.5 μm. Next, the red color resist film was exposed through a mask using an i-ray stepper NSR-2205i12D (NA=0.63) (manufactured by Nikon), developed with a 2.38 mass % TMAH aqueous solution for 60 seconds, rinsed with ultrapure water for 20 seconds, and then dried to form a 100 μm×100 μm rectangular pattern. The residue of the red color resist on the lower layer of the color filter around the rectangular pattern was observed using a scanning electron microscope S-9260 (manufactured by Hitachi High Tech Nologs). The evaluation results of the residue level when compared with Comparative Example 6 are shown in Table 1. The residue level of the red color resist residue observed on the lower layer of the color filter was evaluated at three levels: "less", "more", and "same" compared with Comparative Example 6.

[0111] Table 1

[0112]

[0113] According to the results of Table 1, the film formed by the resin composition of the present invention has high solvent resistance and high transparency. In addition, on the film formed by the resin composition of the present invention, there is little residue of the color resist, and the film formed by the resin composition of the present invention has an excellent effect of suppressing the generation of the residue of the color resist. On the other hand, with respect to the film formed by the resin composition modulated in Comparative Example 1, although it is highly transparent, the solvent resistance is insufficient. With respect to the film formed by the resin composition modulated in Comparative Examples 2 to 4, although it is highly solvent resistant and highly transparent, the reliability is insufficient. With respect to the film formed by the resin composition modulated in Comparative Examples 5 and 6, although it is highly solvent resistant, highly transparent and highly reliable, the residue level is the benchmark or more than the benchmark level. With respect to the film formed by the resin composition modulated in Comparative Example 7, although it is highly solvent resistant and highly transparent, the residue level is the same as the benchmark. With respect to the film formed by the resin composition modulated in Comparative Example 8, although it is highly soluble and highly transparent, the residue level is more than the benchmark level.

[0114] Industrial Availability

[0115] The resin composition of the present invention is suitable as a material for forming a color filter lower film, a color filter upper film, a filler-dispersed resist lower film, etc. in devices such as CCD image sensors, CMOS image sensors, liquid crystal displays, and organic EL displays. In addition, when a color resist pattern is formed on a color filter lower film formed from the resin composition of the present invention, the generation of color resist residues can be suppressed, which is useful for improving the quality and yield of devices equipped with color filters.

Claims

1. A resin composition comprising a homopolymer having a structural unit represented by the following formula (1), a crosslinking compound having at least two alkoxyalkyl groups in one molecule, a photoacid generator, a surfactant, and an organic solvent, The crosslinking compound is a compound having a nitrogen atom alkylated with an alkoxy group. The content of the crosslinking compound is 40% to 60% by mass relative to the content of the homopolymer, and the content of the photoacid generator is at least 0.8% by mass relative to the sum of the contents of the homopolymer and the crosslinking compound. In the formula, R 1 It represents an alkyl group having 1 to 6 carbon atoms and having at least one hydroxyl group as a substituent. 2 . The resin composition according to claim 1 , wherein the acid generated by the photoacid generator is a superacid having an acid dissociation constant pKa of less than −7. 3 . The resin composition according to claim 1 , wherein the acid generated by the photoacid generator is a Bronsted acid. 4 . The resin composition according to claim 1 , wherein the photoacid generator is N-(trifluoromethanesulfonyloxy)-1,8-naphthalimide or a derivative thereof. 5 . The resin composition according to claim 1 , wherein the photoacid generator is a diphenyl[4-(phenylthio)phenyl]sulfonium salt compound.

6. A method for manufacturing a device having a color filter, comprising the following steps: A step of coating the resin composition according to any one of claims 1 to 5 on a substrate; The resin composition is pre-baked at 75° C. to 110° C., exposed to near-ultraviolet rays, and then post-baked at 75° C. to 110° C. to form a color filter lower layer film; and A step of forming a color filter on the color filter underlayer film using a color resist.

7. The method for manufacturing a device with a color filter according to claim 6 further comprises the following steps: a step of coating the resin composition on the color filter; and a step of pre-baking the resin composition at 75°C to 110°C, exposing it to near-ultraviolet light, and then post-baking it at 75°C to 110°C to form an upper film of the color filter. 8 . The method for manufacturing a device having a color filter according to claim 6 , wherein the pre-baking and the post-baking are performed at 100° C. or lower.

Citation Information

Patent Citations

  • Curable composition for flattened film, and flattened film

    JP2000344866A

  • Flattened film-forming composition

    JP2008031370A

  • Resin compositions

    WO2013005619A1

  • Display device, display module, method for manufacturing display device, and method for manufacturing display module

    WO2017203885A1

  • Chemically amplified positive resist composition and patterning process

    CN105301905A